Anorectal biofeedback: an effective therapy, but can we shorten the course to improve access to treatment?. (March 2019) - Mazor, Yoav; Kellow, John E.; Prott, Gillian M.; Jones, Michael P.; Malcolm, Allison
Background: Instrumented anorectal biofeedback (BF) improves symptoms and quality of life in patients with faecal incontinence and defecation disorder-associated chronic constipation. However, demand for BF greatly outweighs availability, so refinement of the BF protocol, in terms of the time and resources required, is of importance. Our aim was to evaluate the outcomes of an abbreviated BF protocol in patients with defecation disorder-associated chronic constipation and/or faecal incontinence compared to standard BF. Methods: Data were collected from consecutive patients ( n = 31; age 54 ± 15; 29 females; 61% functional constipation) undergoing an intentionally abbreviated BF protocol, and compared in a 1:2 ratio with 62 age, gender and functional anorectal disorder-matched control patients undergoing a standard BF. Outcomes included change in symptoms, physiology, patient satisfaction and quality of life. Results: On intention to treat, patients in both protocols showed significant improvement in symptom scores and the magnitude did not differ between groups. Impact on quality of life, satisfaction and control over bowel movements improved in both protocols, but satisfaction improved to a greater extent in the standard BF protocol ( p = 0.009). Physiological parameters were unchanged after BF apart from improvement in rectal sensation in the standard BF group compared to abbreviated BF ( p ⩽ 0.002). Conclusions: Abbreviated anorectal BF offered to patients travelling from far away was not different to a standard BF in providing substantial, at least short term, improvements in symptoms of constipation and faecal incontinence, quality of life and feeling of control over bowel movements. Refinement of the standard BF protocol according to individual patient phenotypes and desired outcomes warrants further study in order to maximize efficacy and improve access for patients.